2021
DOI: 10.1007/s11661-020-06115-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microstructural Morphology on Formability, Strain Localization, and Damage of Ferrite-Pearlite Steels: Experimental and Micromechanical Approaches

Abstract: This paper attempts to predict how the microstructural features and mechanical properties of the individual constituents affect the deformation behavior and formability of ferrite-pearlite steels under quasi-static loading at room temperature. For this purpose, finite element simulations using representative volume elements (RVEs) based on the real microstructures were implemented to model the flow behavior of the ferrite-pearlite steels with various microstructural morphologies (non-banded and banded). The ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 48 publications
2
11
0
Order By: Relevance
“…More recently, a study was performed on ferritic-pearlitic based steel and found that the predicted results was in good agreement with the experimental results [31]. They found that the microstructural morphology plays a vital role in strain partitioning, strain localization and formability of the ferritic-pearlitic steels [31].…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…More recently, a study was performed on ferritic-pearlitic based steel and found that the predicted results was in good agreement with the experimental results [31]. They found that the microstructural morphology plays a vital role in strain partitioning, strain localization and formability of the ferritic-pearlitic steels [31].…”
Section: Introductionmentioning
confidence: 71%
“…It can be said that the OOF2 provides a better transition between the mechanical/thermal behavior of a heterogeneous material at the macro-scale and the mechanical/thermal response of its constituent phases. It provides adequate information about microstructures/ phases (volume fraction, distribution, orientation) to ensure a realistic assessment of thermo-mechanical properties [30][31][32]. More recently, a study was performed on ferritic-pearlitic based steel and found that the predicted results was in good agreement with the experimental results [31].…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…The results presented in the study by Brandaleze [26] show that an increased proportion of ferrite in the microstructure (or a decrease in the carbon content of steel) prevents a decrease in the distance between the cementite lamellae in pearlite, which has a negative effect on the ductility. In addition, the crystal grain size [27], microstructural morphology [28], micro alloying [29] and distance between cementite lamellae [30,31] have a strong influence on the mechanical properties and formability/workability of ferritic-pearlitic steels. In general, it can be said that a microstructure that increases material strength tends to reduce ductility, and vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…However, in their case, the dominant nucleation mechanism took place in the soft ferritic base. Based on tests performed under different tensile stress conditions (from uniaxial to biaxial plane tension), Isavand and Assempour [28] found that microstructural damage is mostly caused by considerable plastic deformation of ferrite grains located near pearlite colonies. Intense plastic deformation of ferrite grains is a consequence of a severe deformation incompatibility between the soft and hard phases (ferrite and pearlite).…”
Section: Introductionmentioning
confidence: 99%